Enhanced Group Delay of the Pulse Reflection with Graphene Surface Plasmon via Modified Otto Configuration - Guimei Li; Qiwei Liu; Yue Liu; Yueying Wei; Rui Weng; Yuxiang Zhou; Leyong Jiang (Advances in Condensed Matter Physics)
In this paper, the group delay of the transverse magnetic (TM) polarized wave reflected from a modified Otto configuration with graphene surface plasmon is investigated theoretically. The findings show that the optical group delay in this structure can be enhanced negatively and can be switched from negative to positive due to the excitation of surface plasmon by graphene. It is clear that the negative group delay can be actively tuned through the Fermi energy of the graphene. Furthermore, the delay properties can also be manipulated by changing either the relaxation time of graphene or the distance between the coupling prism and the graphene. These tunable delay characteristics are promising for fabricating grapheme-based optical delay devices and other applications in the terahertz regime.